Behaviors perceived as mobbing by the instructors assigned in special education institutions - ŞAHSUVAROĞLU, NECDET TUNA (ELSEVIER SCIENCE BV, 2012)
The objective of present research is to detect the behaviors perceived as mobbing by the instructors assigned in special education institutions. 280 instructors collectively constitute the sampling of research. In this study a survey that exhibits demographic features of the mobbing victims and mobbing actors in addition to Behaviors Amongst Primary Education Institutions survey have been used. Research findings have manifested that a majority of people (67,5%) exhibiting mobbing behaviors are the managers; most of them (67,5%) are between ages 23 35 and mobbing behaviors are less frequently observed parallel to the increase in age; between ages 36 48 the ratio is (22,9%) while the ratio falls to (%9,6) for age 49 and above). It has also been detected that individuals who commonly perform mobbing behaviors (61,1%) are the ones that have been working in the same institution for less than 5 years.
Keywords: Mobbing; special education